Thermally conductive resin composition

By using diamond particles A with specific coating films and diamond particles B with uncoated films in thermally conductive silica gel compositions, the problem of difficulty in improving thermal conductivity and emission performance in the prior art is solved, and the effects of low viscosity and high thermal conductivity are achieved.

JP2025065941APending Publication Date: 2025-04-22SEKISUI CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023175484
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

When existing thermally conductive silica gel compositions use diamond particles as fillers, it is difficult to improve thermal conductivity and emission performance at the same time, especially because the surface of diamond particles lacks active groups and is difficult to react with silanol coupling agent, resulting in difficulty in reducing viscosity.

Method used

Thermal conductive silica compositions are used that contain diamond particles A with a specific coating film and diamond particles B with an uncoated film, wherein the surface coating film of diamond particles A comprises a metal oxide or metal, and the average particle size of diamond particles A is smaller than diamond particles B.

Benefits of technology

The thermally conductive silicone compositions are achieved with low viscosity and high thermal conductivity, while improving emission performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025065941000001
    Figure 2025065941000001
  • Figure 2025065941000002
    Figure 2025065941000002
  • Figure 2025065941000003
    Figure 2025065941000003
Patent Text Reader

Abstract

To provide a thermally conductive resin composition containing diamond particles, the thermally conductive resin composition exhibiting superior dischargeability and high thermal conductivity.SOLUTION: A thermally conductive resin composition comprises a resin, diamond particles A having a coating film on at least part of their surface, and diamond particles B having no coating film, wherein the coating film includes at least one selected from the group consisting of metal oxides and metals, and the volume average particle diameter of the diamond particles A is smaller than the volume average particle diameter of the diamond particles B.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermally conductive resin composition for use in, for example, a heat dissipation member. [Background technology]

[0002] Conventionally, heat dissipation materials have been widely used to efficiently dissipate heat from electronic devices. As electronic circuits become more highly integrated and the amount of heat generated by electronic devices increases, the importance of heat dissipation materials is growing for the purpose of improving the performance of electronic devices and preventing their breakdown. Among heat dissipation materials, materials that transfer heat from IC chips and the like to heat sinks are sometimes called TIMs (Thermal Interface Materials). TIMs are generally resin compositions of binder resins and thermally conductive fillers, and are available in the form of sheets and greases.

[0003] In general, in order to improve heat dissipation, it is necessary to highly fill a resin composition with a thermally conductive filler. However, when the thermally conductive filler is highly filled, the viscosity of the resin composition increases, and the ejection properties of the resin composition when ejected from a syringe, for example, deteriorate. In order to solve this problem of high viscosity, a method is known in which the surface of the thermally conductive filler is treated with a silane coupling agent.

[0004] Patent Document 1 discloses an invention relating to a thermally conductive silicone rubber composition characterized by comprising silicone rubber dispersed therein a thermally conductive inorganic filler that has been surface-treated with a silane coupling agent of a specific structure, and describes that the composition has the effects of reducing the viscosity of the molding slurry, reducing the compression set of the molded product, and improving the tear strength. Patent Document 2 discloses an invention relating to a method for producing a silica-coated aluminum nitride particle-dispersed resin composition using silica-coated aluminum nitride obtained through a specific coating step and a heat treatment step, and describes that the composition can form a cured product having excellent moisture resistance, thermal conductivity, and heat resistance. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 11-209618 [Patent Document 2] JP 2020-73622 A Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, from the viewpoint of improving heat dissipation, resin compositions using diamond particles, which are known as a filler with high thermal conductivity, have been investigated. However, diamond particles have few reactive groups on the surface, and therefore have poor reactivity with silane coupling agents, and the method of using a coupling agent as disclosed in Patent Document 1 makes it difficult to reduce viscosity and does not improve dischargeability. In addition, as disclosed in Patent Document 2, it is possible to cover the filler surface with an inorganic component such as silica, but there is a concern that the coating will reduce thermal conductivity.

[0007] Therefore, an object of the present invention is to provide a thermally conductive resin composition containing diamond particles, which has good dischargeability and high thermal conductivity. [Means for solving the problem]

[0008] As a result of intensive research, the inventors have found that the above-mentioned problems can be solved by a thermally conductive resin composition comprising diamond particles A having a specific coating film on at least a portion of their surface and diamond particles B not having the coating film, wherein the volume average particle diameter of the diamond particles A is smaller than the volume average particle diameter of the diamond particles B, and have completed the present invention. That is, the present invention provides the following [1] to [8].

[0009] [1] A thermally conductive resin composition comprising a resin, diamond particles A having a coating film on at least a portion of their surface, and diamond particles B having no coating film, wherein the coating film comprises at least one type selected from the group consisting of metal oxides and metals, and the volume average particle diameter of the diamond particles A is smaller than the volume average particle diameter of the diamond particles B. [2] The thermally conductive resin composition according to the above [1], further comprising an organosilicon compound having a hydrolyzable group directly bonded to a silicon atom in the thermally conductive resin composition. [3] The thermally conductive resin composition according to the above [1] or [2], wherein the coating film contains at least one selected from the group consisting of silica and alumina. [4] The thermally conductive resin composition according to any one of the above [1] to [3], wherein the thickness of the coating film on the diamond particles A measured by the following measuring method is 300 nm or less. (Measuring method: A cross-sectional image of one diamond particle A in the thermally conductive resin composition is observed, and the average value of the thicknesses of the coating film at any 10 points is taken as the film thickness.) [5] The thermally conductive resin composition according to any one of the above [1] to [4], wherein the content of diamond particles A relative to the total volume of filler contained in the thermally conductive resin composition is 3 to 40% by volume. [6] The thermally conductive resin composition according to any one of the above [1] to [5], wherein the coated filler has a volume average particle size of 50 μm or less. [7] The thermally conductive resin composition according to any one of the above [1] to [6], wherein a total filling rate of all fillers contained in the thermally conductive resin composition is 70 volume % or more. [8] The thermally conductive resin composition according to any one of the above [1] to [7], wherein the resin is selected from the group consisting of silicone resins and epoxy resins. Effect of the Invention

[0010] According to the present invention, it is possible to provide a thermally conductive resin composition containing diamond particles, which has good dischargeability and high thermal conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the present invention will be described with reference to an embodiment. [Thermal conductive resin composition] The thermally conductive resin composition of the present invention contains a resin, diamond particles A having a coating film on at least a portion of the surface, and diamond particles B having no coating film. The coating film contains at least one type selected from the group consisting of metal oxides and metals, and the volume average particle size of the diamond particles A is smaller than the volume average particle size of the diamond particles B. The present invention will be described in detail below.

[0012] <Diamond particles> The thermally conductive resin composition of the present invention contains, as a filler, diamond particles A having a coating film on at least a portion of the surface thereof, and diamond particles B having no coating film. The diamond particles A have a coating film on at least a portion of their surface, and the coating film contains at least one type selected from the group consisting of metal oxides and metals. Diamond particles B are diamond particles that have not been coated. Therefore, unlike diamond particles A, diamond particles B are diamond particles that do not have a coating film containing at least one selected from the group consisting of metal oxides and metals. The thermally conductive resin composition of the present invention contains the diamond particles A and diamond particles B, and the volume average particle size of the diamond particles A is smaller than the volume average particle size of the diamond particles B. Therefore, it is possible to increase the thermal conductivity while lowering the viscosity of the thermally conductive resin composition.

[0013] Diamond particle A has a smaller volume average particle diameter than diamond B that does not have a coating film. Diamond particles with a smaller volume average particle diameter generally have a relatively large specific surface area, and usually tend to cause the composition to have a high viscosity. On the other hand, by coating diamond particles with a small volume average particle diameter with the above coating film, compatibility with resin is greatly improved. Therefore, it is considered that the use of diamond particles A with a coated surface can suppress the increase in viscosity of the thermal conductive resin composition. The thermally conductive resin composition of the present invention contains diamond particles B that have a relatively large volume average particle size and do not have a coating film. Diamond particles B have a large volume average particle size, so they have high thermal conductivity, and do not have a coating film, so they do not cause a decrease in thermal conductivity due to the coating film. Diamond particles B have a small specific surface area, so they do not significantly increase the viscosity of the composition even if they do not have a coating film. Furthermore, by combining diamond particles A having a small volume average particle diameter with diamond particles B having a large volume average particle diameter, the overall filling amount of diamond particles can be increased, and as a result, the thermal conductivity can be improved.

[0014] The coating film contains at least one selected from the group consisting of metal oxides and metals. The metals and metal oxides are not particularly limited. Specific metals include transition metals such as Ti, Cr, V, Mn, Nb, W, Mo, Fe, Co, Ni, Pd, Pt, Rh, Ta, Re, Hf, Zr, U, and Ce. Specific metal oxides include magnesium oxide, titanium oxide, iron oxide, silicon oxide, and aluminum oxide. The metal also includes semimetals such as silicon.

[0015] Among the above, metal oxide is preferred.When metal oxide is used for coating film, diamond particle A can be easily mixed with resin, and the reactivity of coating film and silane coupling agent described later can be enhanced.Therefore, especially when thermally conductive resin composition contains silane coupling agent, diamond particle A can be more easily mixed with resin, especially silicone resin, and thus the thermal conductivity of thermally conductive resin composition can be easily increased or the viscosity can be easily reduced.

[0016] As the metal oxide, silica and alumina are preferred, and among them, silica is preferred.By forming a coating film with silica, the reactivity to the silane coupling agent described later can be further improved, and viscosity and thermal conductivity can be further improved.In addition, silica and alumina are preferred in the metal oxide because they are neutral and do not cause redox reaction, and can effectively prevent the thermal deterioration of resin such as silicone resin. The metal and metal oxide in the coating film may be porous or non-porous, and the silica in the coating film may be amorphous or crystalline silica, but is preferably amorphous silica. The metals and metal oxides described above may be used alone or in combination of two or more in the coating film.

[0017] In the present invention, the coating film on the diamond particles A preferably has a thickness of 300 nm or less, more preferably 4 nm or more and 300 nm or less, even more preferably 7 nm or more and 150 nm or less, and even more preferably 10 nm or more and 100 nm or less. When the thickness of the coating film is equal to or less than the upper limit, the thermal conductivity of the thermal conductive resin composition is likely to be increased, whereas when the thickness of the coating film is equal to or more than the lower limit, the viscosity of the thermal conductive resin composition is likely to be decreased.

[0018] The thickness of the coating film can be measured by observing the cross-sectional image of one diamond particle A in the thermally conductive resin composition, and taking the average thickness of the coating film at any 10 points as the thickness. The thickness of the coating film can be adjusted by appropriately selecting the processing conditions when forming the coating film, which will be described later. For example, when forming the coating film by the sol-gel method, the thickness can be adjusted by appropriately setting the concentration of the silica precursor and the curing agent in the processing agent. In addition, in the CVD, ALD, electrodeposition, etc., the thickness can be adjusted by appropriately setting the amount of metal or metal oxide attached to the surface of the diamond particle.

[0019] The coating film of diamond particle A may cover a part of the surface of the diamond particle as the core, but it is preferable to cover most of the surface of the diamond particle, and more preferable to cover the entire surface of the diamond particle. The viscosity of the composition is easily reduced by covering most or the entire surface of the diamond particle with the coating film. Specifically, the coverage of the diamond particle surface by the coating film is preferably 50% or more, more preferably 70% or more, and even more preferably 98% or more. The higher the coverage, the better, and the upper limit is 100%. The coverage can be calculated from a cross-sectional image of diamond particle A.

[0020] The coating film may be a coating film formed from the above metals and metal oxides. Typically, the coating film may be a coating film mainly composed of a compound selected from the group consisting of the above metals and metal oxides. Here, the main component may mean that the content of the metal and metal oxide is, for example, 50% by mass or more, preferably 70% by mass or more, and more preferably 90% by mass or more and 100% by mass or less of the entire coating film.

[0021] <Volume average particle size> In the present invention, the volume average particle size of the diamond particles A and diamond particles B contained in the thermally conductive resin composition may be as follows, from the viewpoint of reducing the viscosity of the composition and improving the thermal conductivity. The volume average particle size of the diamond particles A is preferably 50 μm or less, more preferably from 1 μm to 40 μm, and further preferably from 5 μm to 30 μm. Although the volume average particle size of the diamond particles A is relatively small, the diamond particles A have a coating film on their surfaces, and therefore can suppress an increase in the viscosity of the composition. The volume average particle size of diamond particles B is preferably 10 μm or more and 150 μm or less, more preferably 15 μm or more and 100 μm or less, and more preferably 20 μm or more and 50 μm or less. Diamond particles B have a relatively large volume average particle size and have no coating film on the surface, and therefore can increase the thermal conductivity of the composition.

[0022] In the present invention, the volume average particle diameter of the diamond particles A is smaller than the volume average particle diameter of the diamond particles B. This makes it possible to increase the thermal conductivity while decreasing the viscosity of the thermally conductive resin composition. The difference between the volume average particle diameter of diamond particles B and the volume average particle diameter of diamond particles A (volume average particle diameter of diamond particles B - volume average particle diameter of diamond particles A) is preferably 5 μm or more and 60 μm or less, and more preferably 10 μm or more and 40 μm or less. In addition, the ratio of the volume average particle diameter of diamond particles A to the volume average particle diameter of diamond particles B (volume average particle diameter of diamond particles A / volume average particle diameter of diamond particles B) is preferably 0.1 or more and 0.9 or less, and more preferably 0.2 or more and 0.7 or less.

[0023] Regarding diamond particles A, diamond particles having a coating film with one type of volume average particle diameter may be used as a raw material to be blended into the thermally conductive resin composition, or diamond particles having coating films with two or more different volume average particle diameters may be used in combination. Similarly, for diamond particles B, one type of uncoated diamond particles with a volume average particle diameter may be used as a raw material to be blended into the thermal conductive resin composition, or two or more types of uncoated diamond particles with different volume average particle diameters may be used in combination.

[0024] In this specification, the volume average particle size is the average particle size obtained by averaging the particle sizes on a volume basis, and can be obtained, for example, by measuring the particle size distribution by a laser diffraction method. As a measuring device, for example, a "laser diffraction / scattering type particle size distribution measuring device" manufactured by Microtrack Bell can be used. Regarding the method of calculating the volume average particle size, the particle size (d50) when the cumulative volume is 50% may be used as the volume average particle size. In addition, the diamond particles are used without agglomeration, for example, when crystalline diamonds synthesized by a high-temperature, high-pressure method as described below are used. In such cases, the above average particle size can also be said to be the average particle size of the primary particles of the diamond particles.

[0025] <Types of diamond particles> The diamond particles used for the core part of the diamond particles A with coating film except the coating film, and the diamond particles B without coating film may be as-grown particles, or may be crushed diamond particles obtained by crushing as-grown particles, or may be other diamond particles, and two or more of these may be used together.In addition, generally, as-grown particles are crystalline diamond particles that maintain the shape at the time of synthesis without crushing, and have a polyhedral shape.Crushed diamond particles are obtained by crushing crystalline diamond particles, and generally have an angular shape due to crushing.

[0026] Among the above, the diamond particles used for the core part excluding the coating film of the diamond particles A with coating film, and the diamond particles B without coating film are preferably crushed diamond particles.When crushed diamond particles are used, all diamond particles may be crushed diamond particles, but crushed diamond particles and particles other than crushed diamond particles such as as-grown particles may be used together.

[0027] The metal oxide and metal may be formed into a film on the surface of the diamond particle constituting the core of diamond particle A by chemical vapor deposition (CVD), atomic layer deposition (ALD), electrodeposition, sputtering, the sol-gel process, plating, or the like. The sol-gel method is preferably used, for example, when the coating film is formed of silica. By using the sol-gel method, non-porous amorphous silica can be formed as a coating film on the surface of the diamond particles. In the sol-gel method, when a coating film is formed with silica, a treatment agent containing a silica precursor such as tetraalkoxysilane, a hardener, a catalyst, etc., which is mixed as necessary, is attached to the surface of diamond particles, and a coating film made of silica is formed by hydrolysis, dehydration condensation, etc. In this case, more specifically, diamond particles are immersed in a treatment agent containing a hardener in advance, and after stirring for a predetermined time as necessary, a silica precursor is further added to the treatment agent, and further stirring for a predetermined time as necessary, the treatment agent containing the silica precursor is attached to the diamond particles, and hydrolysis, dehydration condensation, etc. are performed. In addition, a commercially available product may be used as the treatment agent, and the "Protector S" series manufactured by Okuno Chemical Industries Co., Ltd. may be used. Furthermore, when the coating film is made of alumina, it is preferable to employ CVD, ALD, or the like.

[0028] The diamond particles used for the core of diamond particle A are typically synthetic diamond, and are preferably crystalline diamond particles.As mentioned above, crystalline diamond particles can be as-grown particles or crushed diamond particles, but are preferably crushed diamond particles. The synthetic diamond particles may be synthesized by detonation method or high-temperature high-pressure method, but it is preferable to synthesize by high-temperature high-pressure method. By synthesizing diamond particles by high-temperature high-pressure method, diamond particles can be obtained without aggregation. In addition, by synthesizing by high-temperature high-pressure method, crystalline diamond particles can be easily obtained.

[0029] In the high-temperature and high-pressure method, in practical terms, carbon raw material such as graphite can be crystallized and synthesized under high temperature and high pressure in the presence of at least one metal catalyst selected from iron, nickel, cobalt, and chromium, preferably in the presence of iron catalyst. The diamond synthesized in this way is generally polyhedral in shape. In addition, the diamond synthesized by crystallization under high temperature and high pressure can be crushed as necessary to obtain crushed diamond particles as described above. The diamond particles synthesized by the high-temperature and high-pressure method can be washed with an acid or reduced using hydrogen gas as necessary. The diamond particles that form the cores of the diamond particles A and the diamond particles B that do not have a coating film may be commercially available products.

[0030] <Blend amount> The total content of diamond particles A and diamond particles B in the thermally conductive resin composition is preferably 10 to 95 volume %, more preferably 25 to 85 volume %, and even more preferably 40 to 75 volume %, from the viewpoint of achieving both a decrease in viscosity and an increase in thermal conductivity of the composition. Here, "volume %" refers to the volume % relative to the total volume of the reference. The volume of each component can be calculated from the weight and density (true density) of each component. The content of the diamond particles A relative to the total filler contained in the thermally conductive resin composition is preferably 0.5 to 60% by volume, more preferably 1 to 50% by volume, and further preferably 3 to 40% by volume. The content of diamond particles B relative to the total volume of fillers contained in the thermally conductive resin composition is preferably 10 to 98% by volume, and more preferably 20 to 95% by volume.

[0031] (Other fillers) The thermally conductive resin composition of the present invention may further contain fillers other than the diamond particles A and diamond particles B (hereinafter, also referred to as "other fillers"). By containing other fillers, the overall filling rate of the fillers can be improved, for example, the thermal conductivity can be increased, and the heat dissipation can be improved. As the other fillers, thermally conductive fillers that have high thermal conductivity and can increase the thermal conductivity of the thermally conductive resin composition can be preferably used. From the viewpoint of improving thermal conductivity, the thermal conductivity of the other fillers is preferably 8 W / (m·K) or more, more preferably 20 W / (m·K) or more, and even more preferably 30 W / (m·K) or more. The upper limit of the thermal conductivity is not particularly limited, and is, for example, 2500 W / (m·K). The thermal conductivity can be measured by a periodic heating thermoreflectance method using a thermal microscope manufactured by Bethel Co., Ltd. on the cross section of the inorganic particles cut by a cross section polisher.

[0032] In addition, it is preferable to use other fillers that have low electrical conductivity from the viewpoint of insulation. Examples of other inorganic particles include carbides, nitrides, oxides, hydroxides, and carbon-based materials other than coated diamond.

[0033] Examples of carbides include silicon carbide, boron carbide, aluminum carbide, titanium carbide, and tungsten carbide. Examples of nitrides include silicon nitride, boron nitride, aluminum nitride, gallium nitride, chromium nitride, tungsten nitride, magnesium nitride, molybdenum nitride, and lithium nitride. Examples of oxides include iron oxide, silicon oxide (silica), alumina, aluminum oxide such as boehmite, magnesium oxide, titanium oxide, cerium oxide, and zirconium oxide. Examples of hydroxides include aluminum hydroxide, calcium hydroxide, and magnesium hydroxide. Examples of carbon-based materials include carbon black, graphite, graphene, fullerene, carbon nanotubes, and carbon nanofibers. In addition, talc, which is a silicate mineral, can also be used. These other fillers may be used alone or in combination of two or more kinds.

[0034] From the viewpoint of thermal conductivity and insulation, the other filler is preferably at least one selected from aluminum oxide, magnesium oxide, boron nitride, talc, aluminum nitride, and graphene, more preferably at least one selected from aluminum oxide, magnesium oxide, and aluminum nitride, and further preferably aluminum oxide. As the aluminum oxide, alumina is typically used.

[0035] The volume average particle size of the other fillers is preferably smaller than the volume average particle size of the above-mentioned diamond particles A. By reducing the average particle size of the other fillers, the spaces between the diamond particles can be filled more appropriately with the other fillers, and this promotes heat conduction between the diamond particles, thereby improving thermal conductivity. The volume average particle size of the other fillers is, for example, 50 μm or less, preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 20 μm or less, from the viewpoint of appropriately filling the spaces between the diamond particles and facilitating improvement of thermal conductivity. The volume average particle diameter of the other fillers is not particularly limited to a lower limit, but is, for example, 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, and even more preferably 3 μm or more. By making the volume average particle diameter of the other fillers equal to or more than the above lower limit, it becomes easier to prevent thickening and the like while maintaining high thermal conductivity of the thermal conductive resin composition.

[0036] The other fillers may be used in combination with two or more fillers having different volume average particle diameters, as long as the total volume average particle diameter of the other fillers contained in the thermal conductive resin composition is as described above. The other inorganic particles can be determined to contain two or more fillers having different average particle diameters by the appearance of two or more peaks in the particle size distribution. In addition, when the other filler contains two or more types of fillers having different volume average particle diameters, the volume average particle diameter of each filler is preferably in the range of 0.1 μm or more and 100 μm or less, preferably in the range of 0.2 μm or more and 50 μm or less, and more preferably in the range of 0.4 μm or more and 25 μm or less.

[0037] The shape of the other filler is not particularly limited, and may be any of plate-like, scale-like, needle-like, fibrous, tubular, spherical, crushed, polygonal, and irregular shapes, but is preferably spherical or nearly spherical. The other filler is spherical or nearly spherical, which makes it easier to increase the filling rate and reduces friction between the fillers, making it easier to reduce the viscosity of the thermally conductive resin composition. Specifically, the other filler may have a sphericity of, for example, 0.5 or more, preferably 0.55 or more, and more preferably 0.6 or more. The upper limit of the sphericity is not particularly limited, and is 1. The sphericity of the filler can be determined by examining an electron microscope photograph of the filler, calculating the diameter of a circle equal to the projected area of ​​the particle / the diameter of the smallest circle circumscribing the projected image of the particle for 300 particles, and averaging these values.

[0038] When the thermally conductive resin composition contains other fillers, the filling rate of the other fillers may be appropriately adjusted so that the total filling rate of all fillers falls within the range described below, and is preferably 50% by volume or less, more preferably 30% by volume or less, and even more preferably 20% by volume or less, based on the total volume of the thermally conductive resin composition. By making it below these upper limits, a certain amount or more of diamond particles can be blended into the thermally conductive resin composition, making it easier to improve the thermal conductivity. In addition, the filling rate of the other fillers is preferably 2% by volume or more, more preferably 5% by volume or more, and even more preferably 10% by volume or more. By making it above these lower limits, it is easier to demonstrate the effect of blending the other fillers. In this specification, the term "filling rate" refers to the volume percent relative to the total volume of the thermally conductive resin composition.

[0039] The total filling rate of all fillers (i.e., the total content of diamond particles A, diamond particles B, and other fillers) is, for example, 25% by volume or more, preferably 30% by volume or more, more preferably 50% by volume or more, and even more preferably 70% by volume or more, based on the total volume of the thermally conductive resin composition. By making the total filling rate of the fillers equal to or more than these lower limits, the thermal conductivity can be increased. In addition, in the present invention, by using other fillers in addition to the diamond particles, it is also possible to achieve a high filling rate of 70% by volume or more. When the filling rate is 70% by volume or more, the fillers come into contact with each other in the composition (percolation), and the thermal conductivity becomes particularly good. The total filling rate of all fillers is, for example, 96% by volume or less, preferably 92% by volume or less, and more preferably 88% by volume or less. By making it equal to or less than the upper limit, the filler can be easily dispersed appropriately in the resin component, and the thermal conductive resin composition can be prevented from thickening.

[0040] When the thermally conductive resin composition contains other fillers, the content of the other fillers is, from the viewpoint of insulation and thermal conductivity, preferably 5% by volume or more, more preferably 10% by volume or more, and even more preferably 15% by volume or more, based on the total volume of the above fillers (i.e., the total of diamond particles A, diamond particles B, and other fillers is 100% by volume), and is preferably 60% by volume or less, more preferably 50% by volume or less, even more preferably 40% by volume or less, and even more preferably 30% by volume or less.

[0041] Moreover, from the viewpoint of reducing viscosity and improving thermal conductivity, the volume average particle diameter of the coated filler contained in the thermal conductive resin composition of the present invention is preferably 50 μm or less, more preferably 1 μm or more and 40 μm or less, and even more preferably 5 μm or more and 30 μm or less. Here, the coated filler refers to the above-mentioned diamond particles A, and also to other fillers that have a coating film similar to diamond particles A.

[0042] <Resin> The resin contained in the thermally conductive resin composition of the present invention is a component that holds the above-mentioned diamond particles A, diamond particles B, and other fillers, and is a component that serves as a matrix. The resin may be a curable resin or a non-curable resin such as a thermoplastic resin. It may also be an elastomer resin. The curable resin may be moisture curable, thermosetting, or photocurable, but is preferably thermosetting. The resin is preferably liquid. The liquid resin may be one that becomes solid when cured, or may be non-curable and remain liquid in the heat dissipation member. The liquid resin refers to a component that is liquid at room temperature (25°C) and normal pressure (1 atm). The resin may be any compound other than the compound used as a dispersant, which will be described later.

[0043] Examples of the resin include silicone resin, epoxy resin, acrylic resin, urethane resin, phenol resin, unsaturated polyester resin, polyimide resin, polypropylene resin, polyethylene resin, poly(1-)butene resin, polypentene resin and other polyolefin resins, polyethylene terephthalate and other polyester resins, polystyrene resin, acrylonitrile-butadiene-styrene (ABS) resin, ethylene-vinyl acetate copolymer (EVA), polyamide resin, polyvinyl chloride resin (PVC), and the like. The resin may be an elastomer resin, and specific examples thereof include acrylonitrile butadiene rubber, ethylene-propylene-diene rubber, ethylene-propylene rubber, natural rubber, polybutadiene rubber, polyisoprene rubber, polyester-based thermoplastic elastomer, polyurethane-based thermoplastic elastomer, styrene-based thermoplastic elastomer, etc. The elastomer resin may be in a liquid state or a solid state. The resins may be used alone or in combination of two or more. Among the above, the resin is preferably at least one selected from the group consisting of silicone resin and epoxy resin, and more preferably silicone resin. Silicone resin is hydrophobic and therefore easily blends with the diamond particle surface having few functional groups, and epoxy resin is easily blended with the diamond particle surface having few functional groups, which makes it easier to improve the fluidity of the thermally conductive resin composition.

[0044] (Silicone resin) The silicone resin may be a non-curable silicone resin or a curable silicone resin, but is preferably a curable silicone resin. The curable silicone resin may be either a condensation curable silicone resin or an addition reaction curable silicone resin, but is preferably an addition reaction curable silicone resin. The silicone resin is also preferably a silicone rubber. The addition reaction curing type silicone resin preferably comprises a silicone compound as a base agent and a curing agent that cures the base agent. The silicone compound used as the base agent is preferably an organopolysiloxane having an alkenyl group, more preferably an organopolysiloxane having a vinyl group. The number of alkenyl groups in one molecule of the organopolysiloxane is preferably 2 or more, and more preferably contains alkenyl groups at both ends. Specific examples of organopolysiloxanes having vinyl groups include organopolysiloxanes having vinyl groups at both ends, such as polydimethylsiloxane having vinyl groups at both ends, polyphenylmethylsiloxane having vinyl groups at both ends, a dimethylsiloxane-diphenylsiloxane copolymer having vinyl groups at both ends, a dimethylsiloxane-phenylmethylsiloxane copolymer having vinyl groups at both ends, and a dimethylsiloxane-diethylsiloxane copolymer having vinyl groups at both ends.

[0045] The curing agent used in the addition reaction curing silicone resin is not particularly limited as long as it can cure the silicone compound, which is the main agent, but is preferably an organohydrogenpolysiloxane, which is an organopolysiloxane having two or more hydrosilyl groups (SiH) in one molecule. The ratio (molar ratio) of the hydrosilyl group to the vinyl group of the silicone compound is preferably 0.3 or more and 5 or less, more preferably 0.4 or more and 4 or less, and even more preferably 0.6 or more and 4 or less. In the thermally conductive resin composition using diamond particles, the reaction between the main agent and the curing agent may not progress due to the diamond particles, but if the molar ratio is 0.6 or more, the reaction will progress sufficiently, and it will be possible to obtain a sufficiently cured cured product.

[0046] Examples of organohydrogenpolysiloxanes include methylhydrosiloxane-dimethylsiloxane copolymers, polymethylhydrosiloxanes, polyethylhydrosiloxanes, methylhydrosiloxane-phenylmethylsiloxane copolymers, etc. These may or may not contain hydrosilyl groups at the ends.

[0047] The silicone resin has a viscosity at 25° C. of preferably 5 mPa·s or more and 1000 mPa·s or less, more preferably 30 mPa·s or more and 700 mPa·s or less, and even more preferably 50 mPa·s or more and 600 mPa·s or less. The viscosity of the silicone resin is preferably measured using a viscometer (BROOKFIELD rotational viscometer DV-E) with a rotor of spindle No. 14 at a rotation speed of 5 rpm and a measurement temperature of 25° C. As described above, when the silicone resin has a base agent and a curing agent, the viscosity of the mixture of the base agent and the curing agent at 25° C. should be within the above range, but the viscosity of the base agent and the curing agent at 25° C. may each be within the above range. When the viscosity range of the silicone resin is within the above range, the viscosity of the resin composition is kept within a predetermined range, and the resin composition can be kept in a certain shape after coating while improving its coatability, so that it can be easily arranged on electronic components, etc. Also, it becomes easy to mix a large amount of heat conductive filler such as diamond particles after properly dispersing it.

[0048] When an addition reaction curing type silicone resin is used as the silicone resin, a curing catalyst is usually blended into the thermally conductive resin composition. Examples of the curing catalyst include platinum catalysts, palladium catalysts, and rhodium catalysts, among which platinum catalysts are preferred. The curing catalyst is a catalyst for curing the silicone compound and the curing agent, which are the raw materials of the silicone resin. The blending amount of the curing catalyst is usually 0.1 to 200 ppm, preferably 0.5 to 100 ppm, based on the total mass of the silicone resin.

[0049] When an addition reaction curing type silicone resin is used as the silicone resin, a curing retarder may be blended into the thermally conductive resin composition. As the curing retarder, a known one can be used, for example, acetylene compounds such as 1-ethynyl-1-cyclohexanol and 3,5-dimethyl-1-hexyne-3-ol, various nitrogen compounds such as tributylamine and tetramethylethylenediamine, organic phosphorus compounds such as triphenylphosphine, oxime compounds, organic chloro compounds, etc. can be mentioned. By suppressing the catalytic activity of the curing catalyst by including a curing retarder, the shelf life and pot life of the thermally conductive resin composition can be extended. The content of the curing retarder in the thermally conductive resin composition is preferably 0.01 parts by mass or more and 2 parts by mass or less, and more preferably 0.1 parts by mass or more and 1 part by mass or less, relative to 100 parts by mass of the silicone resin.

[0050] The silicone resin may be, for example, silicone oil. Examples of silicone oil include methylphenyl silicone oil, dimethyl silicone oil, and modified silicone oil. The silicone oil preferably has a viscosity at 25°C of 5 mPa·s or more and 1000 mPa·s or less, more preferably 30 mPa·s or more and 700 mPa·s or less, and even more preferably 50 mPa·s or more and 600 mPa·s or less.

[0051] Silicone oil is a liquid component at room temperature and normal pressure when blended, and is also a liquid or gel component when used as a heat dissipation member. That is, silicone oil is not cured by a curing agent or the like, and is a substantially non-curable type that remains liquid or gel even after curing. Therefore, when silicone oil is used alone as a resin component or at a relatively high blending ratio, it can make the heat dissipation member formed from the thermally conductive resin composition into a paste.

[0052] (Epoxy resin) The epoxy resin used as the resin is an epoxy compound having at least one epoxy group, preferably two or more epoxy groups. The epoxy compound is a curable resin, and is usually a thermosetting resin. Examples of the epoxy compound include bisphenol type, novolak type, naphthalene type, triphenolalkane type, biphenyl type, aliphatic type, cyclic aliphatic type, halides thereof, and hydrogenated products thereof. In addition, the epoxy resin may be an epoxy compound alone, but the epoxy resin is a resin containing the epoxy compound as the main component and further containing a curing agent. The curing agent is a polyaddition type or a catalyst type. Examples of the polyaddition type curing agent include polyamine curing agents, acid anhydride curing agents, polyphenol curing agents, polymercaptan, and dicyandiamide. Examples of the catalyst type curing agent include tertiary amines, imidazoles, and Lewis acid complexes. These may be used alone or in combination of two or more types. Furthermore, when an epoxy resin is used, the thermally conductive resin composition may be a two-component curing type that is cured by mixing one liquid containing a base agent with a second liquid containing a curing agent.

[0053] The volume ratio of the resin in the thermal conductive resin composition is, for example, 5% by volume or more, preferably 10% by volume or more, more preferably 15% by volume or more, and for example, 70% by volume or less, preferably 50% by volume or less, more preferably 40% by volume or less, based on the total volume of the thermal conductive resin composition.When the volume ratio of the resin is above these lower limits, the resin can adequately hold each filler such as diamond particles A and diamond particles B dispersed in the resin, and the thermal conductive resin composition can maintain a certain shape.In addition, by making it below these upper limits, each filler can be mixed in a certain amount or more in the thermal conductive resin composition.

[0054] <Organosilicon compounds> The thermally conductive resin composition of the present invention preferably further contains an organosilicon compound having a hydrolyzable group directly bonded to a silicon atom (also called a "silane coupling agent"). The silane coupling agent is used as a dispersant. Generally, diamond particles have low reactivity to silane coupling agents, and are difficult to surface-modify with silane coupling agents. However, the diamond particles A of the present invention have the specific coating film described above, and thus have high reactivity to silane coupling agents, making surface modification with silane coupling agents easy. Therefore, when the thermally conductive resin composition contains a silane coupling agent, the diamond particles A are surface-modified with the silane coupling agent, and the diamond particles A become more compatible with resins such as silicone resins. Therefore, the thermally conductive resin composition has higher thermal conductivity and is easier to reduce viscosity. In addition, when the thermally conductive resin composition contains a silane coupling agent and other fillers, the other fillers may also be surface-modified with the silane coupling agent, which makes the other fillers more compatible with the resin, further increasing the thermal conductivity and making it easier to reduce the viscosity.

[0055] When the thermally conductive resin composition of the present invention contains a silane coupling agent, from the viewpoint of facilitating surface modification with the silane coupling agent, the coating film preferably contains any one of nickel, silica, and alumina, and more preferably contains silica. Furthermore, when the filler is highly filled (for example, the total filler filling rate is 70 volume % or more), the viscosity is likely to increase due to the large amount of filler, so from the viewpoint of reducing the viscosity, it is particularly desirable to include a silane coupling agent in the thermally conductive resin composition.

[0056] Examples of the silane coupling agent include organopolysiloxanes having a hydrolyzable group (hereinafter also referred to as "hydrolyzable group-containing organopolysiloxanes") and alkoxysilane compounds, among which hydrolyzable group-containing organopolysiloxanes are preferred. By using the hydrolyzable group-containing organopolysiloxanes, the silane coupling agent becomes more compatible with the silicone resin. Therefore, both the heat resistance and the thermal conductivity are easily improved, and the viscosity is easily reduced. The silane coupling agent may be used alone or in combination of two or more kinds.

[0057] <Hydrolyzable group-containing organopolysiloxane> The hydrolyzable group-containing organopolysiloxane may be linear or branched, or may be a mixture of linear and branched, but is preferably linear.The hydrolyzable group-containing organopolysiloxane is preferably an organopolysiloxane having at least one hydrolyzable group at the molecular chain end, more preferably an organopolysiloxane having at least one hydrolyzable group at only one end, and even more preferably an organopolysiloxane having three hydrolyzable groups at only one end.The hydrolyzable group is preferably a hydrolyzable silyl group, more preferably an alkoxysilyl group, and even more preferably a methoxysilyl group.

[0058] Specifically, the hydrolyzable group-containing organopolysiloxane is preferably a compound represented by the following formula (1). [ka]

[0059] In formula (1), R 1 are each independently any one of an alkyl group having 1 to 20 carbon atoms, a halogenated alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms, 1 may be the same or different. 2are each independently an alkyl group having 1 to 4 carbon atoms, and in each formula, R 2 If there are multiple R 2 may be the same or different. 3 are each independently any one of an alkyl group having 1 to 4 carbon atoms, an alkoxyalkyl group having 2 to 4 carbon atoms, and an acyl group having 2 to 4 carbon atoms, and in each formula, R 3 If there are multiple R 3 may be the same or different. 4 R is an alkyl group having 1 to 8 carbon atoms. 6 represents an oxygen atom or a divalent organic group having 1 to 40 carbon atoms. m is an integer of 3 to 315. In formula (1), a is an integer of 0 to 2.

[0060] In the above formula (1), R 1 The alkyl group in may be linear or branched, or may have a cyclic structure. More specifically, examples of the alkyl group include linear alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, and eicosyl groups, branched alkyl groups such as isopropyl, tertiary butyl, isobutyl, 2-methylundecyl, and 1-hexylheptyl groups, and cyclic alkyl groups such as cyclopentyl, cyclohexyl, and cyclododecyl groups. Examples of halogenated alkyl groups include chloromethyl, 3,3,3-trifluoropropyl, and 3-chloropropyl groups. Examples of aryl groups include phenyl, tolyl, and xylyl groups. Examples of aralkyl groups include benzyl, phenethyl, and 2-(2,4,6-trimethylphenyl)propyl groups. Among these, R 1 is preferably an alkyl group having 1 to 20 carbon atoms, more preferably an alkyl group having 1 to 4 carbon atoms, and further preferably a methyl group. 1Preferably, 80% or more of R are methyl groups, more preferably 90% or more of R are methyl groups. 1 It is more preferable that all of the groups are methyl groups.

[0061] In the above formula (1), R 2 is an alkyl group having 1 to 4 carbon atoms, and R 2 When a is plural (i.e., when a is 2), the plural R 2 may be the same or different. The alkyl group may be linear or branched. 2 is preferably an alkyl group having 1 to 2 carbon atoms, and more preferably a methyl group. Furthermore, a is an integer of 0 to 2, and a is preferably 0 or 1, and more preferably 0.

[0062] In the above formula (1), R 3 is an alkyl group having 1 to 4 carbon atoms, an alkoxyalkyl group having 2 to 4 carbon atoms, or an acyl group having 2 to 4 carbon atoms; R 3 When a is a plurality of R 3 may be the same or different. 3 The alkyl group, alkoxyalkyl group, and acyl group in R may be linear or branched. 3 is preferably an alkyl group having 1 to 4 carbon atoms, and more preferably a methyl group.

[0063] In the above formula (1), R 4 is an alkyl group having 1 to 8 carbon atoms, preferably an alkyl group having 2 to 6 carbon atoms, and more preferably a butyl group. In the above formula (1), R 6is preferably a group represented by the following formula (2), an oxygen atom, or a divalent hydrocarbon group having 1 to 20 carbon atoms, and more preferably a group represented by the following formula (2) or a divalent hydrocarbon group having 1 to 20 carbon atoms. Here, the divalent hydrocarbon group having 1 to 20 carbon atoms is preferably an alkylene group, and the alkylene group may be linear or branched. The divalent hydrocarbon group having 1 to 20 carbon atoms is preferably an alkylene group having 2 to 10 carbon atoms, more preferably an alkylene group having 2 to 8 carbon atoms, and even more preferably an alkylene group having 2 to 4 carbon atoms, and examples thereof include a methylene group, an ethylene group, a propylene group, a butylene group, and a methylethylene group, and among these, an ethylene group is preferable.

[0064] [ka] In formula (2), R 5 is a divalent hydrocarbon group having 1 to 20 carbon atoms, and multiple R 5 may be the same or different. * represents R 1 -Si-R 1 is the bond position to the silicon atom in 2 a (OR 3 ) 3-a is the bond position to the silicon atom. R 5 The divalent hydrocarbon group in R is preferably an alkylene group, and the alkylene group may be linear or branched. 5 is preferably an alkylene group having 2 to 10 carbon atoms, more preferably an alkylene group having 2 to 8 carbon atoms, and even more preferably an alkylene group having 2 to 4 carbon atoms; -CH 2 -CH 2 -CH 2 - or -CH(CH 3 )-CH 2 An alkylene group represented by the formula - is more preferred.

[0065] In formula (1), m represents the number of repetitions and is an integer of 3 to 315, preferably an integer of 4 to 280, more preferably an integer of 5 to 220, and further preferably an integer of 5 to 100.

[0066] <Alkoxysilane compounds> An alkoxysilane compound is a compound having a structure in which, of the four bonds that a silicon atom (Si) has, 1 to 3 are bonded to an alkoxy group, and the remaining bonds are bonded to an organic substituent. The alkoxy group of the alkoxysilane compound is a hydrolyzable group, and examples thereof include a methoxy group, an ethoxy group, a protoxy group, a butoxy group, a pentoxy group, and a hexatoxy group. Among these, an alkoxysilane compound having a methoxy group or an ethoxy group is preferred. From the viewpoint of enhancing affinity with fillers such as the coated diamond particles A, the number of alkoxy groups in the alkoxysilane compound is preferably 3. Therefore, it is more preferable that the alkoxysilane compound is at least one selected from a trimethoxysilane compound and a triethoxysilane compound.

[0067] Examples of functional groups contained in the organic substituent of the alkoxysilane compound include an acryloyl group, an alkyl group, a carboxyl group, a vinyl group, a methacryl group, an aromatic group, an amino group, an isocyanate group, an isocyanurate group, an epoxy group, a hydroxyl group, and a mercapto group.

[0068] In terms of alkoxysilane compound being compatible with silicone resin and increasing the dispersibility of inorganic particles such as coated diamond particles, it is preferable that the alkyl group bonded to silicon atom is an alkylalkoxysilane compound.The carbon number of the alkyl group bonded to silicon atom is preferably 4 or more.In addition, in terms of the viscosity of the alkoxysilane compound itself being relatively low and the viscosity of the thermal conductive resin composition being kept low, it is preferable that the carbon number of the alkyl group bonded to silicon atom is 16 or less.

[0069] Preferred alkylalkoxysilane compounds include n-hexyltrimethoxysilane, n-hexyltriethoxysilane, n-octyltriethoxysilane, and n-decyltrimethoxysilane. Further, examples of alkoxysilane compounds other than alkylalkoxysilane compounds include 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, and 3-phenylaminopropyltrimethoxysilane.

[0070] The silane coupling agent is preferably mixed with the resin in the thermally conductive resin composition and contained in the thermally conductive resin composition. At least a part of the silane coupling agent contained in the thermally conductive resin composition is adsorbed on the surface of the diamond particles A in the thermally conductive resin composition, and the surface of the diamond particles A is preferably modified.

[0071] However, the diamond particles A may be surface-treated in advance with a silane coupling agent before being mixed into the thermally conductive resin composition. The diamond particles A are surface-modified in advance by being surface-treated in advance with a silane coupling agent. Then, the diamond particles A that have been surface-modified in advance may be mixed with a resin to prepare the thermally conductive resin composition.

[0072] The method for performing the surface treatment using a silane coupling agent is not particularly limited, and may be a known method. For example, a wet treatment method, a dry treatment method, an integral method, etc. may be used, but a wet treatment method is preferred. In the wet processing method, for example, diamond particles are added to and mixed with a processing liquid in which a silane coupling agent is dispersed or dissolved in a solvent, and then the silane coupling agent is bonded or adhered to the surface of the diamond particles by drying, heating, washing, etc. The dry treatment method is a surface treatment method without using a solvent. Specifically, a silane compound is mixed with diamond particles and stirred in a mixer or the like, and then the mixture is heated to bond or adhere a silane coupling agent to the surface of the diamond particles.

[0073] (Other additives) The resin composition of the present invention may contain, as necessary, additives generally used in thermally conductive resin compositions, such as a dispersant, an antioxidant, a heat stabilizer, a colorant, a flame retardant, and an antistatic agent.

[0074] (Thermal Conductivity of Thermally Conductive Resin Composition) From the viewpoint of improving thermal conductivity, the thermal conductive resin composition of the present invention preferably has a thermal conductivity of a certain value or more, specifically, preferably 1.5 W / mK or more, more preferably 2 W / mK or more, and more preferably 5.5 W / mK or more. The higher the thermal conductivity, the better, but in practical use, it is, for example, 30 W / mK or less. The thermal conductivity can be measured by the method described in the examples.

[0075] [Heat dissipation materials] The thermally conductive resin composition of the present invention can be used as a heat dissipation member. The heat dissipation member is formed from the thermally conductive resin composition, and when the thermally conductive resin composition is a curable type, the thermally conductive resin composition is formed into a predetermined shape, and then appropriately heated to cure, thereby making it possible to obtain a heat dissipation member molded into a predetermined shape. In addition, even when the thermally conductive resin composition is not a curable type, the thermally conductive resin composition may be formed into a predetermined shape to be used as a heat dissipation member. When the resin composition is used as a heat dissipation member, it may be formed into a thin film, sheet, block, or irregular shape by coating, casting, potting, extrusion molding, or the like, and then appropriately cured as necessary for use. The thermally conductive resin composition of the present invention has a low viscosity and is therefore excellent in processability when formed into a heat dissipation member.

[0076] The heat dissipation member of the present invention is used, for example, inside an electronic device. Since the heat dissipation member of the present invention has good thermal conductivity, when used inside an electronic device, high heat dissipation can be ensured even when a large amount of heat is generated. The heat dissipation member is, for example, disposed on an electronic component and used to dissipate heat generated by the electronic component. The heat dissipation member of the present invention may also be disposed to fill a gap between two opposing members. The two opposing members may, for example, be one electronic component and the other a heat sink for dissipating heat from the electronic component, a housing for an electronic device, a substrate, or the like. The heat dissipation member may also be used as a so-called TIM (Thermal Interface Material). EXAMPLES

[0077] The following describes examples of the present invention, but the present invention is not limited to the following examples.

[0078] The methods for measuring and evaluating the physical properties of the present invention are as follows. <Coating film thickness measurement> After embedding the diamond particles A in epoxy resin, a cross section was prepared using a focused ion beam device (FIB) and the cross section was observed using a scanning electron microscope (SEM). One diamond particle A contained in the thermally conductive resin composition was observed, and the average value at 10 points was calculated. In addition, when the diamond particles A were partially covered with a coating film, the calculation was performed only for the covered area.

[0079] <Volume average particle size> The volume average particle size was determined by measuring the 50% particle size (D50) in the cumulative particle size distribution based on volume. The measuring device used was a laser diffraction / scattering type particle size distribution measuring device (manufactured by Microtrac, "MT3300EXII").

[0080] <Thermal conductivity evaluation> The thermally conductive resin composition obtained in each Example and Comparative Example was immediately applied to a measurement portion of a measuring device to a thickness D of 700 μm, and the thermal resistance value of the thermally conductive resin composition at that time was measured in accordance with ASTM D5470 using a device "DynTIM" manufactured by Mentor Graphics, Inc. Thereafter, the thermal resistance value was similarly measured at thicknesses of 500 μm and 400 μm. The thermal conductivity was calculated from the thermal resistance value obtained at each thickness using the following formula. Formula: Thermal conductivity (W / m K) = ΔD (unit: mm) / ΔW (unit: K cm2 / W) In the examples and comparative examples, experiments were carried out on a system to which alumina was not added and a system to which alumina was added, and each was evaluated according to the following criteria.

[0081] (Evaluation of thermal conductivity of a system without adding alumina) 〇:2W / m·K or more △: 1.5 W / m K or more, less than 2 W / m K ×: Less than 1.5 W / m K

[0082] (Evaluation of thermal conductivity of systems with added alumina) 〇:5.9W / m·K or more △: 5.3 W / m K or more, less than 5.9 W / m K ×: Less than 5.3 W / m K

[0083] <Evaluation of ejection properties> The thermally conductive resin composition obtained in each Example and Comparative Example was filled into a 30 mL syringe (diameter of the tip of the discharge part: 2.0 mm), and then vacuum degassing treatment was performed. Then, a pressure of 0.42 MPa was applied to the syringe using a digital dispenser, and the discharge amount for 10 seconds was measured, and the discharge amount (g) per minute was calculated to obtain the flow rate value (g / min). As the digital dispenser, "ML-5000XII" manufactured by Musashi Engineering Co., Ltd. was used. In the examples and comparative examples, experiments were carried out on a system to which alumina was not added and a system to which alumina was added, and each was evaluated according to the following criteria.

[0084] (Evaluation of ejection properties of a system without added alumina) ◎:16g / min or more ○: 10g / min or more and less than 16g / min △: 9g / min or more and less than 10g / min ×: Less than 9g / min

[0085] (Evaluation of ejection properties of systems containing alumina) ◎:7.5g / min or more ○: 6.5g / min or more and less than 7.5g / min △: 6.0g / min or more and less than 6.5g / min ×: 5.5g / min or more and less than 6.0g / min ××: Less than 5.5g / min

[0086] The components used in each of the Examples and Comparative Examples were as follows. <Resin> Silicone resin A: 100 mPa·s, vinyl group-containing organopolysiloxane, Contains catalytic amount of platinum catalyst, density 0.97g / cc Silicone resin B: 100 mPa·s, a mixture of vinyl-containing organopolysiloxane and SiH-containing organopolysiloxane, containing a small amount of cure retarder, density 0.97 g / cc Epoxy resin (base): 70 mPa·s, epoxy equivalent 268 (g / eq.), ethylene glycol diglycidyl ether (product name "Deconal EX-830", Nagase ChemteX Corporation), density 0.97 g / cc Epoxy resin (hardener): 165 mPa·s, amine value 630 (KOHmg / g), modified aliphatic amine (product name "WA", manufactured by Mitsubishi Chemical Corporation), density 0.97 g / cc

[0087] <Organosilicon compounds> Dispersant 1 (silane coupling agent): In the chemical formula (1), R 1 and R 3 is a methyl group, a=0, R 4 is a butyl group, R 6 has the structure of chemical formula (2), and R5 The one directly bonded to the carbonyl group is an isopropylene group (having a methyl group at the carbonyl α-position and bonded to the siloxane silicon atom in chemical formula (1) at the carbonyl β-position), and the other R 5 Organopolysiloxane with propylene group. Density 0.97g / cc Dispersant 2 (silane coupling agent): 3-glycidoxypropyltriethoxysilane, product number "KBE-403", manufactured by Shin-Etsu Chemical Co., Ltd. Density 0.97g / cc

[0088] <Filler: Diamond particles> Synthetic diamond 1 (uncoated): Tomei Diamond "CMM10-20", volume average particle size 13μm, density 3.52g / cc Synthetic diamond 2 (silica coating): A silica coating was formed on Tomei Diamond's "CMM10-20" (the thickness of the coating is shown in the table (5nm to 300nm)), with a volume average particle size of 13μm and a density of 3.52g / cc. Synthetic diamond 3 (uncoated): Tomei Diamond "CMM40-60", volume average particle size 34.3μm, density 3.52g / cc Synthetic diamond 4 (silica coated): A silica coating was formed on Tomei Diamond's "CMM40-60" (thickness of the coating is 30 nm), volume average particle size is 34.3 μm, density is 3.52 g / cc Synthetic diamond 5 (no coating): Tomei Diamond Co., Ltd., hexahedral as-grown diamond, volume average particle size 55.3μm, density 3.52g / cc Synthetic diamond 6 (silica coated): manufactured by Tomei Diamond Co., Ltd., a silica coating is formed on a hexahedral as-grown diamond (thickness of the coating is 30 nm), volume average particle size is 55.3 μm, density is 3.52 g / cc Synthetic Diamond 7 (uncoated): Tomei Diamond Co., Ltd., hexahedral as-grown diamond, volume average particle size 114μm, density 3.52g / cc

[0089] <Other fillers: Alumina particles> Alumina 1: Admatechs "AO-502", volume average particle size 0.32μm, density 3.94g / cc Alumina 2: "AA-05" manufactured by Sumitomo Chemical Co., Ltd., volume average particle size 0.58 μm, density 3.94 g / cc Alumina 3: "AA-5" manufactured by Sumitomo Chemical Co., Ltd., volume average particle size 6.6 μm, density 3.94 g / cc

[0090] <Examples 1 to 13 and Comparative Examples 1 to 4> A thermally conductive resin composition was obtained by mixing a resin, a filler, and an organosilicon compound according to the formulations shown in Tables 1 and 2. The thermal conductivity and dischargeability of the obtained thermally conductive resin composition were evaluated as described above.

[0091] [Table 1]

[0092] JPEG2025065941000004.jpg229109

[0093] As shown in Examples 1 to 13, the thermally conductive resin composition of the present invention contains diamond particles A having a specific coating film on the surface thereof and diamond particles B having no coating film, and the volume average particle diameter of the diamond particles A is smaller than that of the diamond particles B. The thermally conductive resin composition has low viscosity, good dischargeability, and high thermal conductivity. On the other hand, the comparative thermally conductive resin compositions that do not satisfy the requirements of the present invention, such as those that do not contain diamond particles with a coating film, those that all diamond particles have a coating film, or those that have diamond particles with a coating film that have a larger volume average particle diameter than diamond particles without a coating film, showed poor results in at least one of the ejection properties and thermal conductivity.

Claims

1. The present invention includes a resin, diamond particles A having a coating film on at least a portion of the surface thereof, and diamond particles B having no coating film, the coating film contains at least one selected from the group consisting of metal oxides and metals, A thermally conductive resin composition, wherein the diamond particles A have a volume average particle size smaller than the volume average particle size of the diamond particles B.

2. 2. The thermally conductive resin composition according to claim 1, further comprising an organosilicon compound having a hydrolyzable group directly bonded to a silicon atom.

3. The thermally conductive resin composition according to claim 1 or 2, wherein the coating film contains at least one selected from the group consisting of silica and alumina.

4. 3. The thermally conductive resin composition according to claim 1, wherein the coating film of diamond particles A has a thickness of 300 nm or less as measured by the following measurement method. (Measuring method: A cross-sectional image of one diamond particle A in the thermally conductive resin composition is observed, and the average value of the thicknesses of the coating film at any 10 points is taken as the film thickness.)

5. 3. The thermally conductive resin composition according to claim 1, wherein the content of diamond particles A relative to the total volume of filler contained in the thermally conductive resin composition is 3 to 40 volume %.

6. 3. The thermally conductive resin composition according to claim 1, wherein the coated filler has a volume average particle size of 50 μm or less.

7. 3. The thermally conductive resin composition according to claim 1, wherein a total filling rate of all fillers contained in the thermally conductive resin composition is 70 volume % or more.

8. 3. The thermally conductive resin composition according to claim 1, wherein the resin is selected from the group consisting of silicone resins and epoxy resins.

Citation Information

Patent Citations

  • Heat-conductive silicone rubber composition

    JP1999209618A

  • Method for producing silica-coated aluminum nitride particle dispersion resin composition, and method for producing sheet having cured product thereof, and method for producing power device having sheet

    JP2020073622A